Integration of project management processes at the planning stage to the corporate business processes - Зацерковний, Віталій Іванович; Оберемок, Іван Іванович; Оберемок, Наталія Василівна; Єгорченкова, Наталія Юріївна (Technology audit and production reserves, 2016)
The problem that faced the project manager and project participants in the implementation is that the processes of traditional project management methodology aren’t integrated into the existing system of business processes. The reason for this is the lack of uniform generally accepted project management processes that must be performed on the stage of project planning and use of non-adaptive processes of traditional project management methodologies. The object of the study is the project management processes at the planning stage. It is proposed to integrate a project management processes to business processes at the planning stage. In description of the project management processes in the form of business processes, efficiency of formation of all the processes required for implementation of the planning phase of the project is increased that allow schematically show not only their sequence, but also incoming and outgoing documents required for the proper implementation of the processes, assign responsible in each process and describe the procedure execution processes. Research results are described functions, duties and powers of the roles in the project, defined processes at the planning stage of the project; described procedures for the implementation of each process; described template of outgoing process documents. Research results can be used to form the Rules of project management. This approach to description and organization of management processes at the planning stage allows to systematize the actions of the head of project management and management of the company, in turn, unify a single generally accepted procedure of project implementation, objectively assess the quality of the project management by the project manager, achieving the objectives of the projects.